The Effect of at-Tahaddus ‘anil a'mal al-Yaumiyah Method on Maharatui Kalam of Class VIII Students of SMP IT Lukmanul Hakim - Gani, Fauzia; Yasin, Zohrah; Abdullah, Abdullah (Yayasan Daarul Qimmah Gorontalo, 2023)
This research is a quantitative study that uses a non-experimental research design with the type of expost facto research. Based on the results of research that has been conducted on the effect of the At Tahadduts Anil A'mal Yaumiyah method (X) on Maharatul Kalam (Y) class students, it can be concluded from the results of hypothesis testing that there is no effect of the At Tahadduts Anil A'mal Yaumiyah method (X) on Maharatul Kalam (Y) class VIII students of SMP IT Lukmanul Hakim Gorontalo Regency. This can be seen from the significance value (Sig.) which is 0.691 greater than 0.05. So it can be concluded that Ha is rejected and H0 is accepted.